Anaplastic nephroblastomas express transketolase-like enzyme 1. Issue 5 (12th January 2009) - Wu, H-T; Allie, N; Myer, L; Govender, D
Abstract : Aim: Transketolase-like enzyme 1 (TKTL1) is a glycolytic enzyme that has been found to be upregulated in several tumours, and it is associated with tumour progression. Nephroblastoma is the commonest paediatric renal malignancy and has a good prognosis except for those with anaplasia. To the best of the authors' knowledge, the expression of TKTL1 in nephroblastomas has not been studied before and the aim of this study was to compare the immunoexpression of TKTL1 in anaplastic and non-anaplastic nephroblastomas. Methods: Twenty-eight patients who had nephrectomies for nephroblastomas were studied. Archival formalin-fixed paraffin-wax-embedded tissue sections were stained with monoclonal TKTL1 antibody. Results: Six of the 15 anaplastic nephroblastomas showed staining in 80–100% of the tumour (p = 0.36). None of the 13 non-anaplastic nephroblastomas showed TKTL1 staining in >80% of the tumour. Conclusion: TKTL1 expression is associated with the presence of anaplasia and may be a mechanism via which anaplastic tumour cells thrive under different conditions. Glycolytic inhibitors may play a role in anaplastic nephroblastomas.